A time and space correlated turbulence synthesis method for Large Eddy Simulations - Castro, Hugo Guillermo (2012)
In the present work the problem of generating synthesized turbulence at inflow boundaries of the simulation domain is addresed in the context of the Large Eddy Simulation (LES) method. To represent adequately certain statistical properties of a turbulent process, we propose a synthesized turbulence method which is based on previous works and . For this purpose, time and space correlations are introduced strictly in the mathematical formulation of the synthetic turbulence inflow data. It is demonstrated that the proposed approach inherits the properties of the methods on which it is based while presents some particular advantages as well. The strategy of imposing conditions on the inlet velocity field through turbulence synthesis is implemented in the parallel multiphysics code called PETSc-FEM (http://www.cimec.org.ar/petscfem) primarily targeted to calculations throughout finite elements on general unstructured 2D and 3D grids. We present several numerical tests in order to validate and evaluate the method describing the dynamic phenomena that take place in "real-life" problems, such as a swirling turbulent flow inside a diffuser and the airflow around a vehicle model inside a wind tunnel at high Reynolds number.